Enforceability of judgments against sovereign States: critical analysis of the NML vs. Argentina injunction - Alejandro Gabriel Manzo (Revista Direito GV)
Abstract Sentences against sovereign States are difficult to enforce in courts. The Court of New York, in “NML Capital Ltd. vs. Argentina” (NML), tried to solve this situation with an injunction that blocked the payments of Argentina’s sovereign debt. The specialized literature has theoretically predicted that this injunction would cause harm to third parties and problems with other States. This article empirically corroborates these predictions with the analysis of a trial derived from NML: the “Citibank Argentina” case. The analysis of this case confirms the restraints presented by the literature about the lack of proper consideration of the requirements that the American legal system imposes for the applicability of an injunction that affects third parties and operates extraterritorially. Similarly, this paper argues that there are solid legal reasons for the authorities of third countries to declare inadmissible the extraterritorial effects of an injunction, such as the one obtained by NML, when those effects fall on assets and agents located in these authorities jurisdiction.